2017
DOI: 10.1186/s40035-017-0072-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of exosomes in the pathogenesis of Alzheimer’ disease

Abstract: Exosomes are small vesicles secreted by most cell types including neurons that function in intercellular communication through transfer of their cargo or encapsulate and eliminate unnecessary cellular components and therefore have a broad impact on nerve development, activation and regeneration. In addition, exosomes have been observed to be involved in spreading pathological misfolded proteins, thereby leading to the onset and propagation of disease. Alzheimer disease (AD) is the most common form of dementia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
95
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 76 publications
1
95
0
Order By: Relevance
“…Recent studies have demonstrated the usefulness of this novel biomarker technology for prognosis as well as biological mechanisms for AD in the general population (Paschon et al 2016; Rajendran et al 2006; Riancho et al 2017; Sharples et al 2008; Vingtdeux et al 2012; Xiao et al 2017; Yuyama and Igarashi 2017), and can also be used for studying the propagation of pathology within the brain (Polanco et al 2016; Winston et al 2016). We are hopeful that this novel methodology can shed light on early events in the pathology in DS-AD and hopefully lead to novel intervention or prevention therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated the usefulness of this novel biomarker technology for prognosis as well as biological mechanisms for AD in the general population (Paschon et al 2016; Rajendran et al 2006; Riancho et al 2017; Sharples et al 2008; Vingtdeux et al 2012; Xiao et al 2017; Yuyama and Igarashi 2017), and can also be used for studying the propagation of pathology within the brain (Polanco et al 2016; Winston et al 2016). We are hopeful that this novel methodology can shed light on early events in the pathology in DS-AD and hopefully lead to novel intervention or prevention therapies.…”
Section: Discussionmentioning
confidence: 99%
“…In the heart, cardiomyocytes-derived exosomes can transfer functional glucose transporters and glycolytic enzymes to modulate glucose transport and metabolism in recipient endothelial cells [70]. Microglia can spread protein via exosome secretion and depletion of microglia or inhibition of exosome synthesis was shown to significantly reduce tau propagation in vitro and in vivo [71, 72]. In RPE-endothelial cell interactions, it was demonstrated that ethanol-stressed RPE cells release more exosomes than control cells, and those exosomes contain higher levels of VEGF receptors in their membranes, as well as increased levels of VEGFR-1 and −2 mRNA within the exosome and thus promote vasculogenesis/angiogenesis when they interact with endothelial cells [73].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that myeloid cells can release EVs/MP that spread inflammatory signals both in vitro and in vivo to alter neuronal functions (Harrison-Brown et al, 2016;Nigro et al, 2016;Beneventano et al, 2017;Kumar et al, 2017). Importantly, EV levels are significantly increased following TBI in humans and animal models, as well as in chronic neurodegenerative and autoimmune disorders such as Alzheimer's disease (AD) and multiple sclerosis, supporting the concept that spreading inflammation via EVs release may play a role in these neuropathologies (Taylor and Gercel-Taylor, 2014;Xiao et al, 2017;Pieragostino et al, 2018). Thus, nSMase inhibitors have emerged as new pharmacological agents for preventing release of EVs and thus can modulate inflammation and oxidative stress.…”
Section: Introductionmentioning
confidence: 93%